Bisulfite activated permanganate for oxidative water decontamination. (1st June 2022) - Guan, Chaoting; Guo, Qin; Wang, Zhen; Wei, Xipeng; Han, Bin; Luo, Xiaonan; Pan, Hanping; Jiang, Jin
Highlights: Disputes over reactive intermediates involved in Mn(VII)/bisulfite system were discussed. Key role of dissolved oxygen in organics degradation was elaborated. Degradation performance of contaminants under various conditions was summarized. Activation mechanisms of Cr(VI) and Fe(VI) by bisulfite were compared to Mn(VII). Abstract: Recently, bisulfite-activated permanganate (MnO4 − ; Mn(VII)) process has attracted considerable attention as a novel class of advanced oxidation technology for destruction of organic contaminants in water. However, disputes over the underlying activation mechanism as well as reactive species generated in the Mn(VII)/bisulfite system remain for a long period due to the fairly complex chemistry involved in this system. This article aims to present a critical review on scientific development of the Mn(VII)/bisulfite system, with particular focus on the generation and contribution of various reactive intermediates. Both reactive manganese species (RMnS) (i.e., soluble Mn(III), Mn(V), and Mn(VI)) and radical species (primarily SO4 − ) are identified as the oxidizing components responsible for enhanced degradation of organic contaminants by the Mn(VII)/bisulfite system. Bisulfite plays a dual role of being an activating agent for reactive intermediates generation and acting as a complexing agent to stabilize RMnS. Solution chemistry (e.g., the [Mn(VII)]/[bisulfite] molar ratio, solution pH, the type of contaminants, ligands, and water matrix components) greatly impacts the generation and consumption of RMnS and radicals, thus influencing the degradation kinetics and pathways of organics. Particularly, dissolved oxygen (DO) is a vital factor for driving the oxidation of organics since the absence of DO can block the generation of SO4 − and meantime causes the consumption of RMnS by excess SO3 − as a strong reductant. Interestingly, ferrate (FeO4 2−, Fe(VI)) and hexavalent chromium (CrO4 2− /HCrO4 −, Cr(VI)) that are high-valent metal oxyanions analogous to Mn(VII) can be activated by bisulfite via a similar pathway (i.e. both high-valent metal-oxo intermediates and reactive radicals are involved). Furthermore, key knowledge gaps are identified and future research needs are proposed to address the potential challenges encountered in practical application of the Mn(VII)/bisulfite oxidation technology. Graphical abstract: Image, graphical abstract